The effects of hypomorphic STAT3 on lymphocyte function and intestinal immune regulation - Steward-Tharp, S (2012)
Dominant-negative mutations in signal transducer and activator of transcription 3 (STAT3) underlie the human primary immunodeficiency autosomal dominant hyper IgE syndrome (HIES). A number of aspects of this disease, including the eponymous elevated serum IgE, remain poorly understood. Additionally, work from numerous animal models has suggested STAT3 plays a critical role in the development, regulation and resolution of intestinal inflammation. Human genetic studies have associated this pleiotropic transcription factor with inflammatory bowel disease (IBD), but elucidation of the overall role of STAT3 in intestinal homeostasis has been hindered by the lethality associated with germline deletion. To better understand STAT3 function in both intestinal homeostasis and IgE regulation, we generated bacterial artificial chromosome (BAC)-transgenic mice that expressed a HIES-associated STAT3 allele. Transgenic cells exhibited normal tyrosine phosphorylation of STAT3 following acute cytokine stimuli, but marked inhibition in DNA-binding activity. The mice recapitulated important aspects of HIES, including elevated serum IgE. We identified an intrinsic bias towards IgE class switch recombination (CSR) in transgenic B cells, and a possible role for STAT3 in directly regulating both the immunoglobulin heavy chain locus and key regulators of CSR, such as Id2, an inhibitor of μ-ε switching. The partial loss of STAT3 signaling also led to important changes in intestinal responses, with transgenic mice showing enhanced susceptibility to both dextran sodium sulfate (DSS) and Citrobacter rodentium induced colitis. Following C. rodentium infection, we observed defects in both the early production of certain antimicrobial peptides such as RegIIIγ and resolution of inflammation in late infection, where the bacterial burden was decreasing. Transgenic myeloid cells were hyporesponsive to IL-10, suggesting that hypomorphic STAT3 activity within the intestine destabilizes the system: predisposing to infection and hindering the IL-10 regulatory pathway’s ability to keep inflammatory responses in check. Therefore, our data suggest that STAT3 plays key roles in both CSR and the maintenance of intestinal homeostasis.